Case Studies of Teacher Development : an In-Depth Look at How Thinking About Pedagogy Develops Over Time. - Levin, Barbara B. (Lawrence Erlbaum Associates, 2002)
This book represents the results of a 15-year longitudinal study based on in-depth case studies of the development of four teachers' pedagogical thinking. These studies illustrate how teachers' thinking--about children's behavior, development, learning, a.